Metabolomic profiling of polymyxin-B in combination with meropenem and sulbactam against multi-drug resistant Acinetobacter baumannii - Zhu, Shixing; Zhang, Jiayuan; Song, Chu; Liu, Yuwei; Oo, Charles; Heinrichs, M. Tobias; Lv, Zhihua; Zhu, Yuanqi; Sy, Sherwin K. B.; Deng, Pan; Yu, Mingming (Frontiers in Microbiology, 2022)
Empirical therapies using polymyxins combined with other antibiotics are recommended in the treatment of Acinetobacter baumannii infections. In the present study, the synergistic activities of polymyxin-B, meropenem, and sulbactam as combination therapy were investigated using metabolomics analysis. The metabolome of A. baumannii was investigated after treatment with polymyxin-B alone (2 μg/mL), meropenem (2 μg/mL) alone, combination of polymyxin-B/meropenem at their clinical breakpoints, and triple combination of polymyxin-B/meropenem and 4 μg/mL sulbactam. The triple combination significantly changed the metabolite levels involve in cell outer membrane and cell wall biosynthesis, including fatty acid, glycerophospholipid, lipopolysaccharide, peptidoglycan, and nucleotide within 15 min of administration. In contrast, significant changes in metabolome were observed after 1 h in sample treated with either meropenem or polymyxin-B alone. After 1 h of administration, the double and triple combination therapies significantly disrupted nucleotide and amino acid biosynthesis pathways as well as the central carbon metabolism, including pentose phosphate and glycolysis/gluconeogenesis pathways, and tricarboxylic acid cycle. Taken together, the combination of polymyxin-B, meropenem and sulbactam could enhance the antibiotic effects against MDR A. baumannii. Our findings could help optimize synergistic combinations in antimicrobial therapy.